The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.21764/maeuefd.1000695
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Öğrenme Ortamlarinin Çocuk Ve Öğretmen Perspekti̇fi̇nden Değerlendi̇ri̇lmesi̇

Abstract: Okul öncesi dönem çocukları ve öğretmenlerinin öğrenme ortamlarına ilişkin değerlendirmelerini incelemek amacıyla yürütülen bu çalışma, nitel araştırma yöntemlerinden olgubilim deseninde tasarlanmıştır. Çalışma grubu, ölçüt örnekleme yöntemi ile seçilen, 48-72 aylık 12 çocuktan ve 17 okul öncesi öğretmeninden oluşmaktadır. Veri toplama aracı olarak araştırmacılar tarafından geliştirilmiş demografik bilgi formları ve yarı yapılandırılmış görüşme formları kullanılmıştır. Toplanan veriler yüzde frekans dağılımlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…The family, which constitutes the first social environment of the child, is of primary importance in the development of the child's creativity. The influence of parenting practices and styles, as well parental attitudes on the child's creativity are well-established and supported by research (Dursun & Ünüvar, 2011;Miller & Gerard, 1979;Pugsley & Acar, 2018). Comparing the parenting attitudes and behaviors of highly intelligent and highly creative high school students, Getzels and Jackson (1961) found that more creative students had more supportive parents.…”
Section: The Role Of Parents In Supporting Creativitymentioning
confidence: 91%
“…The family, which constitutes the first social environment of the child, is of primary importance in the development of the child's creativity. The influence of parenting practices and styles, as well parental attitudes on the child's creativity are well-established and supported by research (Dursun & Ünüvar, 2011;Miller & Gerard, 1979;Pugsley & Acar, 2018). Comparing the parenting attitudes and behaviors of highly intelligent and highly creative high school students, Getzels and Jackson (1961) found that more creative students had more supportive parents.…”
Section: The Role Of Parents In Supporting Creativitymentioning
confidence: 91%